STRATEGI BERTAHAN HIDUP NELAYAN-NELAYAN KECIL DESA BATU AMPAR,KECAMATAN PALMATAK, KABUPATEN ANAMBAS - Azizah, Lutfiana Nur; Anugrahini, Triyanti (UI Scholars Hub, 2019)
Common problems faced by fishermen include the limited availability of fish resources, due to over fishing, climate change and the instability of fish selling prices. This condition is also experienced by small fishermen in Batu Ampar Village who carry out traditional fishing activities on the high seas. Facing the limitations of accessible fish resources and the uncertainty of the climate, they made various efforts so that they could survive. The purpose of this study was to describe the survival strategies of small fishermen in Batu Ampar Village in dealing with the problems faced while they were at sea. This research was conducted using a qualitative approach. Through the selection of informants by purposive sampling, in-depth interviews were conducted with 8 fishermen informants. The results showed that the small fishermen of Batu Ampar Village carried out a survival strategy that was reviewed based on survival skills standards when facing various problems at sea. These strategies include fishermen returning home and catching fish near the island, maximizing the use of GPS and fish finders, helping each other with fellow fishermen at sea, approaching oil and gas drilling areas, and utilizing existing equipment.